Acute Kidney Injury and Renal Regional Oxygen Saturation During Pediatric Liver Transplantation - Sinner, Barbara; Banas, Miriam; Brunete-Lorenzo, Clara; Zant, Robert; Knoppke, Birgit; Scherer, Marcus N.; Graf, Bernhard M.; Lunz, Dirk (Annals of Transplantation, 2020)
BACKGROUND Kidney injury is a complication among children undergoing liver transplantation (pLTx). Cystatin C serum concentration seems to be superior to creatinine-based determination of kidney injury in adults and children. Near-infrared spectroscopy (NIRS) technology provides non-invasive and real-time measurement of renal tissue oxygenation. Here, we compared renal tissue oximetry (rSrO₂) with conventional diagnostic criteria cystatin C and creatinine concentration in children undergoing pLTx. MATERIAL AND METHODS rSrO₂ was measured intraoperatively in children undergoing pLTx over the left kidney, and was statistically compared with pre- and postoperative serum creatinine and cystatin C concentrations. RESULTS rSrO₂ was affected by hemoglobin concentration, bilirubin concentration, and FiO₂. Statistical analysis demonstrated that rSrO₂ was significantly reduced in children with preoperative pathologic increased cystatin C concentrations compared to children without (63.7±4.3 vs. 53.4±4.9, p<0.05). We did not detect a significant difference in rSrO₂ between children who developed postoperative renal impairment, either determined by increased postoperative cystatin C concentration, creatinine concentration, or the pRIFLE criteria. Intraoperative increase or decrease in rSrO₂ did not predict the development of postoperative kidney injury. CONCLUSIONS In children with liver failure undergoing pLTx, a preoperative decrease in rSrO₂ indicates compromised renal function. However, intraoperative rSrO₂ is not predictive of postoperative kidney injury.
CRIS-Team Scopus Importer:2020-02-04